The effectiveness of reinforcement sensitivity theory on student motivation through group counseling services - Lestari Lestari; Rita Eka Izzaty (Program Studi bimbingan Konseling PPs UNM Makassar, 2020)
This research aims to determine the effectiveness of the use of Reinforcement Sensitivity Theory (RST) towards increased motivation to learn students through group counseling services. This research uses quantitative approach method with non-equivalent control group design. The research sample amounted to 14 students who have motivational learning problems that have not been expected. The data collection techniques in this study used scale techniques using purposive sampling. Data analysis techniques using Wilxocon test and Mann-Whitney Test. The results of this research show that Reinforcement Sensitivity Theory (RST) through group counseling services proved to be an effective learning motivation for students.